Activated FXR inhibits leptin signaling and counteracts tumor-promoting activities of cancer-associated fibroblasts in breast malignancy - Vircillo, Valentina; Andò, Sebastiano; Catalano, Stefania (My University, 2017)
Cancer-associated fibroblasts (CAFs), the principal components of the tumor stroma, play a central role in cancer development and progression. As an important regulator of the crosstalk between breast cancer cells and CAFs, the cytokine leptin has been associated to breast carcinogenesis. The nuclear Farnesoid X Receptor-(FXR) seems to exert an oncosuppressive role in different tumors, including breast cancer. In this study, we demonstrated, for the first time, that the synthetic FXR agonist GW4064, inhibiting leptin signaling, affects the tumor-promoting activities of CAFs in breast malignancy. GW4064 inhibited growth, motility and invasiveness induced by leptin as well as by CAF-conditioned media in different breast cancer cell lines. These effects rely on the ability of activated FXR to increase the expression of the suppressor of the cytokine signaling 3 (SOCS3) leading to inhibition of leptin-activated signaling and downregulation of leptin-target genes. We further extend our data investigating whether FXR agonist may directly influence CAF phenotype. We demonstrated that FXR is expressed in different CAFs and treatment with GW 4064 is able to induce the transcription of key FXR target genes, including SHP (Small Heterodimer Partner) and BSEP (Bile Salt Export Pump). Interestingly, FXR activation is able to significantly reduce CAF motility, without influencing their proliferation capabilities. Accordingly, IPA (Ingenuity Pathway Analysis) on FXR-modulated genes highlighted cellular movement as the most significantly represented biologic process and evidenced a marked reduction in the activity of Rho signaling and Integrin proteins, with activation z-score of -1, -0,5 respectively. Moreover, our data showed a reduction in stress fibers formation in GW 4064 -treated CAFs. Activated FXR is able to reduce tumor promoting effects of CAFs on breast cancer cells, due to the ability of GW 4064 to reduce CAF secreted soluble factors, including IGF-1 (Insulin Growth Factor-1), FGF-9 (Fibroblast Growth Factor 9), TGF-3 (Transforming Growth Factor Beta 3) and others key mediators involved in the crosstalk tumor-stroma. Indeed, our data demonstrate how ER-breast cancer cell lines, MCF-7 and T47D, cocoltured with conditioned media derived from GW4064-treated CAFs, exhibit a significantly reduced anchorage-independent growth and migration. In vivo xenograft studies, using MCF-7 cells alone or co-injected with CAFs, showed that GW4064 administration markedly reduced tumor growth. Thus, FXR ligands might represent an emerging potential anti-cancer therapy able to block the tumor supportive role of activated fibroblasts within the breast microenvironment
Dottorato di Ricerca in Medicina Traslazionale. Ciclo XXIX
Keywords: Leptin; Breast; Cancer